Evaluation of therapeutic efficacy of epidural steroid injections in lumbar spine with patients of chronic low back pain - Jati, Saket; Danish, Mohammad; Sheikh, Tanveer; Varun, Ajay (International Journal of Research in Orthopaedics, 2017)
Background: Intervertebral disc herniation, spinal stenosis, intervertebral disc degeneration without disc herniation, and post lumbar surgery syndrome are the most common diagnoses of chronic persistent low back and lower extremity symptoms, resulting in significant economic, societal, and health care impact. Epidural injections are one of the most commonly performed interventions in managing chronic low back pain (LBP) along with surgical intervention. Cost effectiveness and affordability has become the cornerstone of evidence-based medicine, and has an influence on coverage decisions, especially in developing countries such as India. LBP is a common problem. The aim of this study was to find the therapeutic efficacy of epidural steroid injections (ESIs) in chronic LBP. Methods: 50 patients presenting with LBP with or without radiculopathy treated with ESIs were prospectively followed for average duration of 12 months. Results: Fifty patients were included in this study with average age 51.02±7.1, out of these 26 (52%) were males and 24 (48%) females. Significant pain relief (>50%) was demonstrated in 43 (71%) of patients and functional status improvement was demonstrated by a reduction of 40% in Oswestry disability index (ODI) score in 49 (81%) patients. Conclusions: ESIs are very effective and significantly reduce pain in patients with chronic function-limiting LBP.